The geographical distribution of Church schools in England - Gay, JD; Greenough, J (Culham College Institute, 2000)
This report maps the distribution of Church of England and Roman Catholic primary schools and Church of England secondary schools in England as they were in 1995. The report first sketches their historical background and then maps their distribution as a percentage of the total number of schools for each local authority and then of the percentage of pupils in them. There are separate analyses of the distribution of Church of England aided schools, of controlled schools and of both types combined, of Roman Catholic schools and then of all types of church school. In all there are 51 maps. A brief commentary is also provided. The proportion of Church of England primary schools ranges widely from under 5% in Gateshead, Sunderland and seven of the London boroughs to 50% in Oxfordshire, Somerset and Wiltshire. The proportion of Roman Catholic schools in most local authorities is under 10%, but in Kensington and Chelsea, and in four Merseyside authorities, the figure rises to 30% or over. When the contributions of both churches are combined, the highest percentage of church primary schools is found in Wigan and Westminster. The analyses were timely for two reasons. First, legislation had strengthened the position of church schools in relation to local authority powers to reorganise the school sector. Second, the Church of England had just begun a review of its schools under the chairmanship of Lord Dearing. The report provides a very useful backcloth against which later incremental changes can be placed.